MACROECONOMIC EFFECTS OF THE RAW-MATERIAL EXPORT ORIENTATION IN UKRAINE’S AGRICULTURAL SECTOR - SVYNOUS, Ivan; SALO, Inna; BILORUSETS, Lesia; ZELENA, Maria (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article investigates the profound macroeconomic consequences of the predominance of raw-material exports within the structural composition of Ukraine’s agricultural sector. It is argued that the long-standing export strategy, primarily oriented toward the external supply of grains, oilseeds, and minimally processed commodities, has entrenched a persistent dependence of the national economy on global price fluctuations and has generated a spectrum of systemic risks. Based on the analysis of manifestations of the “Dutch disease” effect, the study identifies adverse repercussions for the exchange rate of the national currency, the degradation of processing industries, technological stagnation, and the reinforcement of the extractive nature of trade.The research delineates the transmission mechanisms through which agricultural raw-material specialization affects key macroeconomic indicators—GDP, the balance of payments, the investment climate, employment levels in agrarian regions, and the share of foreign trade-generated value added. Special emphasis is placed on the post-2014 period and the consequences of the full-scale war since 2022, which have underscored Ukraine’s critical vulnerability to external shocks, disruptions in logistics, and the fragility of export infrastructure. Empirical evidence demonstrates that countries long reliant on a resource-based development model have faced heightened income volatility, investment instability, and structural impediments to transitioning toward an industrialized economy.The article outlines potential scenarios for the transformation of Ukraine’s agro-export model: the development of processing clusters, the promotion of exports of high value-added products (e.g., finished food industry products), the support of organic farming, the bioeconomy, certification practices, and the adoption of innovative technologies. Pathways to overcoming the “resource trap” are proposed through institutional reform of agricultural policy, the modernization of storage and transport infrastructure, increased investments in education and research, and enhanced coordination among the Ministry of Agrarian Policy, the Ministry of Economy, and export agencies. The study concludes that only a shift from a raw-material export paradigm to an innovation-driven industrial model of development can ensure long-term macroeconomic stability, income growth, currency resilience, and the consolidation of Ukraine’s competitive advantage in the global agricultural market.
Keywords: agricultural raw materials; export model; Dutch disease; macroeconomic stability; value added; processing; agricultural policy; economic security; resource vulnerability; institutional transformation